Inflammatory conditions of the esophagus: an update. Issue 1 (11th August 2020) - Lisovsky, Mikhail
Abstract: A variety of inflammatory disorders involve the esophagus. This commentary discusses the pathology of some forms of esophagitis, with an emphasis on recent developments. The initial section focuses on some common forms of nonreflux esophagitis, including lymphocytic esophagitis and eosinophilic esophagitis. Recent studies suggest that lymphocytic esophagitis may be associated with esophageal motility disorders and gastroesophageal reflux disease. Immunophenotypic features of intraepithelial lymphocytes may be helpful in distinguishing these conditions. Updates on the criteria and the limitations of histologic approach to the diagnosis of eosinophilic esophagitis are presented and new diagnostic adjuncts are discussed. In the remaining section, novel entities, such as IgG4‐related esophagitis, are discussed. IgG4‐related esophagitis has been recognized as a cause of esophageal lymphoplasmacytic inflammation. Increased understanding of esophageal inflammation remains an important goal that likely will lead to new approaches in the therapy of inflammatory esophageal diseases. Abstract : Inflammatory disorders of the esophagus are commonly encountered in clinical practice and are usually treatable. Since the spectrum of clinical and endoscopic manifestations of these disorders is limited, histologic evaluation plays an important role in establishing an accurate diagnosis and guiding patient management. This commentary provides brief updates on the pathology of some of the common or recently described inflammatory entities.